Depression and Behavioral Changes Associated with Social Media Dependency During COVID-19 Pandemic Among University Students in Bangladesh: A Cross- Sectional Study - Karmokar, Sushmita; Islam, Md. Ashraful; Muktadir, Mohammad Hamid Al; Hasan, Rakibul; Tareq, Abu Montakim; Amin, Mohammad Nurul; Emran, Talha Bin (Makara Journal of Health Research, 2021)
Background: With its rapid spread, the coronavirus disease 2019 (COVID-19) pandemic had a detrimental effect on students’ psychological well-being, depression, and behavioral changes due to indefinite educational leaves, lockdowns, restricted outdoor activities, and excess use of social media. This study aims to assess the relationship of social media exposure with the psychological well-being, depression, and behavioral changes of Bangladeshi university students. Methods: A web-based cross-sectional survey was carried out on 530 students from June 17 to July 10, 2020, to evaluate psychological well-being, depression, behavioral changes, and social media exposure via self-reported measures. Results: The prevalence of factors were as follows: poor psychological well-being was 24.9%; moderate to severe depression was 56.6%; severe behavioral changes was 32.1%; and of moderate to severe addiction to social media exposure was 38.3%. All factors were positively associated with social media exposure. Multivariate logistic regression showed that the addiction of participants to social media was 7.488 times higher with severe behavioral changes (OR: 7.488; 95% CI 4.708–11.909), 2.299 times higher with poor psychological functioning (OR: 2.299; 95% CI 1.421–3.721), 30.54 times higher with severe depressed (OR: 30.54; 95% CI 15.0–62.177) than that of individuals without such symptoms. Conclusions: The above findings imply that the government needs to pay greater attention to improve the overall situation of Bangladeshi university students.